Image 1_APOL1 is a novel prognostic biomarker in thyroid cancer and correlates with immune infiltration.jpeg - Jianting Man (22678730) (2025)
Background Although apolipoprotein 1 (APOL1) expression is upregulated in several types of cancers, including thyroid cancer (THCA), its specific role in THCA remains unclear. The aim of the present study was to analyze whether APOL1 could serve as a prognostic marker and predictor of immune cell infiltration (ICI) in THCA. Methods APOL1 expression was assessed using TCGA and GTEx data, based on data from The Cancer Genome Atlas (TCGA). The diagnostic and prognostic value of APOL1 was assessed using Kaplan-Meier survival curves, receiver operating characteristic curves, Cox regression analysis and enrichment analysis in R. Kyoto Encyclopedia of Genes and Genomes and Gene Ontology were used to determine APOL1-related pathways. Furthermore, the correlation between APOL1 expression and ICI, as well as immune checkpoint genes, was investigated. Western blotting, cell counting Kit-8, wound healing assays, Transwell assays and 5-EdU were used to examine APOL1 expression and function in THCA. Results Abnormally elevated expression of APOL1 was observed in THCA tissues based on the data from TCGA and GTEx. Functional biological analysis indicated a strong connection between APOL1 and immune signatures. Additionally, APOL1 expression showed a correlation with infiltration of various immune cell types, including macrophages, neutrophils, dendritic cells, T and B cells, Th1/2 cells, CD8 T cells and Tregs. The results of western blotting confirmed upregulated APOL1 expression in THCA tissues. In vitro experiments showed that knockdown of APOL1 promoted THCA proliferation, invasion and migration. APOL1 serves as a valuable prognostic biomarker and is related to disease progression and ICI in THCA. Conclusions In this study, we innovatively explored the potential association between APOL1 and the immune microenvironment, and demonstrated that APOL1 expression is upregulated in THCA tissues. Knockdown of APOL1 in THCA cells results in promoted proliferation and migration. Additionally, APOL1 may regulate ICI in the THCA microenvironment.